Diagnostic value of the molecular detection of Sarcoptes scabiei from a skin scraping in patients with suspected scabies. - Moonsuk Bae; Ji Yeun Kim; Jiwon Jung; Hye Hee Cha; Na-Young Jeon; Hyun-Jung Lee; Min Jae Kim; Sung Eun Chang; Sung-Han Kim (Public Library of Science (PLoS), 2020)
Scabies is a highly contagious parasitic disease associated with long-term residence in nursing homes, and it is a public health burden worldwide. However, atypical skin manifestations are frequent and the widely used diagnostic test based on microscopic examinations has limited sensitivity. We evaluated the diagnostic value of polymerase chain reaction (PCR) from skin scraping in patients with suspected scabies. Adult patients with suspected scabies, unrelated diseases or healthy volunteers were enrolled at a tertiary hospital, in Seoul, South Korea, from December 2017 through October 2018. We classified participants based on the consensus criteria established by the International Alliance for the Control of Scabies in 2018; confirmed (microscopic mite detection), clinical (scabies burrow or typical lesions with two history features including itch and close contact with scabies patients), suspected scabies (typical lesion with one history feature or atypical lesion with two history features), or no scabies. PCR was performed on the skin scrapings to target the cytochrome c oxidase subunit 1 (cox1) gene of Sarcoptes scabiei. A total of 47 participants, 33 with suspected scabies, 10 with unrelated diseases, and 4 healthy volunteers were enrolled. Of the 33 patients, 22 were classified as confirmed scabies, 2 as clinical scabies, 6 as suspected scabies, and 3 as no scabies. The sensitivities of the microscopic examination were 100%, 92%, and 73% in confirmed scabies; confirmed and clinical scabies; and confirmed, clinical, and suspected scabies, respectively (p = 0.006). The sensitivities of PCR were 86%, 83%, and 80% in confirmed scabies; confirmed and clinical scabies; and confirmed, clinical, and suspected scabies, respectively (p = 0.59). The specificity of the scabies PCR in the no scabies control was 100% (95% CI = 80-100).PCR testing for scabies may be helpful in the improvement of sensitivity for the diagnosis of scabies by clinical criteria.